Political Communication of Legislative Candidate in Affecting Political Participation in the North Aceh District (Komunikasi Politik Calon Legislatif dalam Memengaruhi Partisipasi Politik Masyarakat di Kabupaten Aceh Utara) - nfn Fauzi (BBPSDMP KOMINFO MAKASSAR, 2018)
This study discusses the political communication of legislative candidates in influencing the political participation of the community in North Aceh District. Political communication is a process of communication or the process of giving symbols or symbols of communication containing political messages that have implications affect the attitudes and behavior of audiences who become political targets. Legislative candidates are elected by the general election through legislative elections normally proposed by political parties. This research uses survey method with mixmethod approach, quantitative and qualitative. Based on the results of the research, political communication of legislative candidates influences the political participation of the people in Aceh Utara Regency by 33.2% and the rest is influenced by other things that are not examined. Coefficient of positive value means the more effective political communication of legislative candidates, then the increasing political participation of the community. Likewise, the results of interviews with political figures show that political messages are arranged in such a way by the legislative candidates submitted at the time of the campaign either face to face or through mass media and the ability to communicate or convey messages may affect the participation of the people to vote for the legislative candidate in legislative elections.Penelitian ini membahas mengenai komunikasi politik calon legislatif dalam memengaruhi partisipasi politik masyarakat di Kabupaten Aceh Utara. Komunikasi politik merupakan suatu proses komunikasi atau proses pemberian lambang-lambang atau simbol-simbol komunikasi yang berisikan pesan-pesan politik yang memiliki implikasi memengaruhi sikap dan tingkah laku khalayak yang menjadi target politik. Calon legislatif dipilih masyarakat melalui pemilihan umum legislatif yang biasanya diajukan oleh partai politik. Penelitian ini menggunakan metode survei dengan pendekatan mixmethod, kuantitatif dan kualitatif. Berdasarkan hasil penelitian, komunikasi politik calon legislatif memengaruhi partisipasi politik masyarakat di Kabupaten Aceh Utara sebesar 33,2% dan sisanya dipengaruhi hal-hal lain yang tidak diteliti. Koefisien bernilai positif artinya semakin efektif komunikasi politik calon legislatif, maka semakin meningkat partisipasi politik masyarakat. Begitu juga dengan hasil wawancara dengan tokoh politik menunjukkan bahwa pesan-pesan politik yang disusun dengan sedemikian rupa oleh calon legislatif yang disampaikan pada saat kampanye baik secara tatap muka maupun melalui media massa dan kemampuan berkomunikasi atau menyampaikan pesan dapat memengaruhi partisipasi masyarakat untuk memilih calon legislatif tersebut dalam pemilu legislatif.